2019
DOI: 10.1097/meg.0000000000001292
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting antiviral hepatitis C virus treatment perturbation of the metabolic milieu

Abstract: Objective Hepatitis C virus (HCV), cirrhosis, and HCV medications including direct-acting antivirals (DAAs) ±ribavirin may all influence the metabolic milieu. While interferon-based regimens improve glucose tolerance, evidence is limited on DAAs. Cases of elevated lactate have recently been reported in patients treated with DAAs, and lactic acidosis is a known complication of antivirals used to treat hepatitis B virus and HIV. Patients and methods Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Overall, a numerical increase was observed from baseline in both total cholesterol (P=0.06) and triglyceride levels (P=0.40). And patients with diabetes were noted to have an elevation in cholesterol after treatment (P=0.05 by Wilcoxon test; n=10), but no significant change in triglycerides (P=0.50 by Wilcoxon test; n=7) [48].In line with these results, several clinical studies provided strong evidence that lipoprotein levels and liver lipid accumulation were inclined to normalize after the initiation of combination therapy including sofosbuvir/ribavirin, sofosbuvir/ledipasvir, asunaprevir/daclatasvir and grazoprevir/elbasvir. These modifications appear to be associated with significant improvement of steatosis and atherogenesis [49][50][51][52][53].…”
Section: Recovery Of Metabolic Damagementioning
confidence: 68%
“…Overall, a numerical increase was observed from baseline in both total cholesterol (P=0.06) and triglyceride levels (P=0.40). And patients with diabetes were noted to have an elevation in cholesterol after treatment (P=0.05 by Wilcoxon test; n=10), but no significant change in triglycerides (P=0.50 by Wilcoxon test; n=7) [48].In line with these results, several clinical studies provided strong evidence that lipoprotein levels and liver lipid accumulation were inclined to normalize after the initiation of combination therapy including sofosbuvir/ribavirin, sofosbuvir/ledipasvir, asunaprevir/daclatasvir and grazoprevir/elbasvir. These modifications appear to be associated with significant improvement of steatosis and atherogenesis [49][50][51][52][53].…”
Section: Recovery Of Metabolic Damagementioning
confidence: 68%
“…In the majority of cases, liver function, fibrosis, and stiffness improve after SVR through both interferon and DAA treatments (44)(45)(46)(47). Though the majority of patients do not experience changes in glucose homeostasis (48), some patients experience improvement of diabetic control after achieving SVR (15,47,49). However, we describe three cases in which the treatment of HCV appears to have induced the development of insulin resistance or islet cell destruction.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 91%
“…Lacerda et al found that 1-year post-treatment levels of total cholesterol, LDL, VLDL and triglycerides were significantly elevated in patients who had achieved SVR [77]. Similarly, a study by Driedger et al, carried out on 442 HCV patients who were treated with DAA, found that the level of serum cholesterol and triglycerides were also elevated after achieving SVR [78]. The role of HCV genotype on post-SVR hypercholes-terolemia has been also investigated.…”
Section: Lipid Profile/circulating Hypocholesterolemiamentioning
confidence: 99%